Implementation Of Default Judgment In Article 19 Letter C Of Government Regulation Number 9 Of 1975 At The Religious Court Of Lubuk Pakam - Anshari, Muhd. Khumaidi El; Rokan, Mustapa Khamal; Yazid, Imam (UNIVERSITAS PAKUAN, 2023)
Each husband and wife has the right to file for divorce in the Religious Court in accordance with Government Regulation Number 9 Article 19 Letter C of 1975 and Compilation of Islamic Law Number 1 Article 116 of 1991 concerning the grounds for divorce. This is stated in the judgment of the Religious Court of Lubuk Pakam Number 2612/Pdt.G/2019/PA-Lpk. The plaintiff is NL residing in Deli Serdang Regency, and the defendant is MSHN residing in Class II B Lubuk Pakam Penitentiary. It is explained in the case summary that the plaintiff and the defendant entered into marriage on February 12, 2017, and were blessed with 2 (two) children. Initially, the plaintiff's and defendant's household was harmonious and peaceful, but on April 27, 2018, the defendant was detained by the police and sentenced to 9 (nine) years in prison for the crime of